Polymorphisms in key innate immune genes and their effects on measles vaccine responses and vaccine failure in children from Mozambique - Clifford, H.; Hayden, C.; Khoo, S.; Naniche, D.; Mandomando, I.; Zhang, Guicheng; Richmond, P.; Le Souëf, P. (2012)
Despite an effective vaccine, measles remains a major health problem globally, particularly in developing countries. More than 30% of children show primary vaccine failure and therefore remain vulnerable to measles. Genetic variation in key innate pathogen recognition receptors, such as the measles cell entry receptors CD46 and SLAM, measles attachment receptor DC-SIGN, the antiviral toll-like receptors (TLR)3, TLR7 and TLR8, and the cytosolic antiviral receptor RIG-I, may significantly affect measles IgG antibody responses. Measles is still highly prevalent in developing countries such as those in Africa however there is no previous data on the effect of these innate immune genes in a resident African population. Polymorphisms (n= 29) in the candidate genes were genotyped in a cohort of vaccinated children (n= 238) aged 6 months-14 years from Mozambique, Africa who either had vaccine failure and contracted measles (cases; n= 66) or controls (n= 172). Contrasting previous associations with measles responses in Caucasians and/or strong evidence for candidacy, we found little indication that these key innate immune genes affect measles IgG responses in our cohort of Mozambican children. We did however identify that CD46 and TLR8 variants may be involved in the occurrence of measles vaccine failure. This study highlights the importance of genetic studies in resident, non-Caucasian populations, from areas where determining the factors that may affect measles control is of a high priority. © 2012 Elsevier Ltd.